THE DIFFERENCES BETWEEN MEN AND WOMEN’S LANGUAGE IN THE DEVIL WEARS PRADA MOVIE - Tri Puspa Juwita; Dyah Sunggingwati; Nita Maya Valiantien (Fakultas Ilmu Budaya Universitas Mulawarman, 2018)
ABSTRACT This research with the title investigated the differences between men and women’s language feature and the consistency of the using of that language features by each gender. This research used the theory from Coates (2004) about men’s language features and Lakoff, quoted by Holmes (2003) about women’s language. The researcher got the data from every dialogue by main and supporting characters. The research design in this research used qualitative method from Mack et al (2005). The data source of this research got from the dialogue of men and women’s characters and the researcher also used books and journals which are related to this research to analyze the data. The technique of data analysis is descriptive method. The researcher draws two conclusions: firstly, this research found that men and women’s character in The Devil Wears Prada movie did not use all of the language features from Coates and Lakoff. Secondly, the researcher found that in some situation, the men and women’s character did not consistent use their own language features. Keywords: features consistency, men’s language, women’s language, The Devil Wears Prada movie ABSTRAK Penelitian ini bertujuan untuk meneliti tentang perbedaan antara bahasa pria dan bahasa wanita dan konsistensi pengunaan tersebut pada masing-masing jenis kelamin. Penelitian ini menggunakan teori dari Coates (2004) tentang bahasa pria dan teori dari Lakoff yang dikutip oleh Holmes (2003) tentang bahasa wanita. Peneliti mendapatkan data dari seluruh percakapan yang dilakukan oleh pemeran utama dan pemeran pendukung. Penelitian ini menggunakan metode kualitatif dari Mack et al (2005). Sumber data diperoleh dari percakapan karakter pria dan wanita dan juga didukung oleh buku dan jurnal yang berkaitan dengan penelitian ini. Cara untuk menganalisis data adalah dengan menggunakan metode deskripsi. Peneliti mendapatkan dua kesimpulan: pertama, ditemukan bahwa karakter pria dan wanita di film The Devil Wears Prada tidak menggunkan seluruh kriteria dari Coates dan Lakoff. Kedua, peneliti menemukan bahwa di beberapa situasi, karakter pria dan wanita tidak konsisten menggunakan karaker bahasa masing-masing gender. Kata kunci: konsistensi karakter, bahasa pria, bahasa wanita, film The Devil Wears Prada